(3SfO GdTjNjf eMeO hCHi HcQ GdOdGFis - (3YHO GdSdGe Hf GdWjH Hf eMeO GdbGOQj GdMSfj GdeZQHj GdaGSj, CHh eMeO,J (B1110 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CSfO dg cd hdi HGdfHi ChUdg hGNJUQ HbQHg haVdg HfHjd MHg GdYdi efRdg s
(3BNQgG (B:s
(3Ke GdUdGI eGdgG EMUGQ eY SdGe hHdg eOQGQ Ydi GdMHjH GdeUWai eMeO QShd QHfG GdYdi GdUeO hBdg jJHY gPG fbWYGJ ai C SGfjO ZjQ eYQha CUMGHgG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B125 - (3U(B127s
(3efXheIs
(3Ke jJHYg ebWYGJ ai CSGfjO eYQha CUMGHgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B235 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs